Strategi Pemasaran Produk Qardh Beragunan Emas dalam Meningkatkan Minat Nasabah pada Bank Syariah Indonesia KCP Medan Aksara - Eka Dian Pratiwi; Abi Waqqosh2; Tri Dessy Fadillah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study evaluates the marketing strategy of the Gold-Backed Qardh product at Bank Syariah Indonesia KCP Medan Aksara with the aim of identifying the effectiveness of the strategy in increasing customer interest. The method used is qualitative with a SWOT analysis approach, which involves interviews with the bank and analysis of marketing documents. The results of the study indicate that the marketing strategy implemented includes appropriate market segmentation, product development in accordance with sharia principles, and effective promotion. The SWOT analysis reveals the strengths of the product in terms of sharia compliance and the stable value of gold as collateral, but also highlights challenges such as increasing market awareness and administrative efficiency. Therefore, an integrated marketing strategy that is responsive to market dynamics can increase customer interest and strengthen the bank's position in the market.